2017
DOI: 10.3390/e19060251
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Entropy Analysis of the Differential RR Interval Time Series Signal and Its Application in Detecting Congestive Heart Failure

Abstract: Cardiovascular systems essentially have multiscale control mechanisms. Multiscale entropy (MSE) analysis permits the dynamic characterization of the cardiovascular time series for both short-term and long-term processes, and thus can be more illuminating. The traditional MSE analysis for heart rate variability (HRV) is performed on the original RR interval time series (named as MSE_RR). In this study, we proposed an MSE analysis for the differential RR interval time series signal, named as MSE_dRR. The motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The overall sensitivities and specificity are comparable with those computed by other methods [8,20,21]. However, the EoE method is able to separate healthy subjects from CHF and AF patients at one time with less data points.…”
Section: Accuracy Of Eoesupporting
confidence: 66%
“…The overall sensitivities and specificity are comparable with those computed by other methods [8,20,21]. However, the EoE method is able to separate healthy subjects from CHF and AF patients at one time with less data points.…”
Section: Accuracy Of Eoesupporting
confidence: 66%
“…Let us demonstrate the usage of EnRE for Detecting Congestive Heart Failure in short segments (N = 500) by MIT-BIH RR database. In [8], it has been shown that the minimal length of an RR-segment, for which it is possible to classify NSR and CHF groups by way of Multiscale Entropy Analysis, is N = 1000.…”
Section: Time Series Entropymentioning
confidence: 99%
“…In both cases, the differences between groups are reliable to the degree of p < 10 -7 . Therefore, proposed generalized form for Robust Entropy Estimator EnRE allows, with high accuracy, to divide NSR and CHF groups in short records (N = 500), which had remained unachieved in [8] by the way of Multiscale Entropy Analysis, and presents additional advantages provided by EnRE in case of structural changes in series (such as sorting). Quality of classification achieved by using two variables EnRE and EnRE(sort) is superior to results received in [8] by way of Multiscale Entropy Analysis for RR segments with length of N = 1000, N = 2000 and N = 5000.…”
Section: Time Series Entropymentioning
confidence: 99%
“…Costa et al [ 9 ] extended multiscale entropy to generalized multiscale entropy by using different moments of the distribution of random variables to coarse-grain the original time series. In 2017, Liu et al [ 10 ] proposed an MSE analysis method for differential RR interval time series signals and distinguished normal sinus rhythm subjects from CHF patients. However, it has been suggested that entropy methods often do not perform satisfactorily when they are used to analyze the non-linear complexity in physiological signals, and the choice of coarse-grained time scales leads to inaccurate estimates of entropy.…”
Section: Introductionmentioning
confidence: 99%